Dribbling skills training model in football games for elementary school age - Tarigan, Herman; Cahyadi, Ardian; Siswoyo, Joan (Journal of Education, Health and Sport, 2021)
The goal achieved from this research and development is to produce a model of soccer dribbling training models for the elementary school age group. This research and development is carried out to be able to obtain information about the development and application of the football dribbling training model for the elementary school level age group. and to find out the effectiveness of the model produced. This research uses Research & Development (R & D) method from Borg and Gall. The subjects in this study were students of SD Negeri 1 Metro Barat from 30 children. The stages in this study are: needs analysis, expert evaluation (initial product evaluation), small group trials, and large group trials (testing fields). Test the effectiveness of the model. With the success of the research proven by questionnaires submitted by experts at 80%, the dribbling training model deserves to be developed in accordance with the research study of the development model of Borg and Gall. Based on the results of the development it can be concluded that: (1) With the soccer dribbling training model for elementary school level children can be developed and applied in dribbling exercises on extracurricular and learning (2) With the soccer dribbling training model for elementary school level that has been developed, there is evidence of an increase of which there are significant differences between before and after getting the model treatment.